Champ the Chimp - Preston, Isabel (Zaner-Bloser, Inc.)
Little Champ the Chimp would like to get a job. Champ went to the desk of his big pal Bob. Champ said, I would like a task to do. Big Bob, can I get a job with you?...
Keywords: Animal Stories